2018
DOI: 10.1038/s41598-018-30094-5
|View full text |Cite
|
Sign up to set email alerts
|

Phenylephrine, a common cold remedy active ingredient, suppresses uterine contractions through cAMP signalling

Abstract: Regulation of uterine contractility is an important aspect of women’s health. Phenylephrine, a selective agonist of the α1-adrenoceptor and a potent smooth muscle constrictor, is widely used in women even during pregnancy to relieve cold-related symptoms, to treat postpartum haemorrhoid, and during routine eye exams. We performed isometric tension recordings to investigate the effect of phenylephrine on mouse uterine contractility. Phenylephrine decreased spontaneous and oxytocin-induced contractions in non-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Additionally, propranolol is a non-selective β-adrenergic receptor antagonist, while metoprolol has a preferential β1-selectivity, hence suggesting that the observed changes in CTM size might be related to the differential effects of propranolol and metoprolol on β2-adrenergic receptor (−AR) signaling. This hypothesis is strengthened by the fact that high concentrations of PE, as used in the present study, has been shown to induce also βAR activation in vivo [67] and to have stimulatory effects on β 2 AR mediated via cAMP [68]. Propranolol as a nonselective β-blocker could therefore attenuate or block the pro-hypertrophic effects of PE in our CTM model.…”
Section: Discussionsupporting
confidence: 53%
“…Additionally, propranolol is a non-selective β-adrenergic receptor antagonist, while metoprolol has a preferential β1-selectivity, hence suggesting that the observed changes in CTM size might be related to the differential effects of propranolol and metoprolol on β2-adrenergic receptor (−AR) signaling. This hypothesis is strengthened by the fact that high concentrations of PE, as used in the present study, has been shown to induce also βAR activation in vivo [67] and to have stimulatory effects on β 2 AR mediated via cAMP [68]. Propranolol as a nonselective β-blocker could therefore attenuate or block the pro-hypertrophic effects of PE in our CTM model.…”
Section: Discussionsupporting
confidence: 53%
“…39 It may seem surprising that phenylephrine, normally stimulat ing α1 adrenergic receptors and Gq/11, should lead to cAMP accumulation, but various reports show that the agonist can also activate β2 receptors, or that other downstream pathways could be activated, for example, Ca 2+ /Calmodulin activation of adenylyl cyclase 1 and 8. 40,41 Increased cAMP levels ac tivate PKA, which we demonstrated to be involved in both phenylephrine-and forskolin-stimulated ATP release ( Figure 3). PKA, in turn, could directly or indirectly phosphorylate and activate Panx1, which has putative recognition sites for both PKA and PKC, 42,43 and Src kinase 7,32 ).…”
Section: Discussionmentioning
confidence: 71%
“…A recent study demonstrated that phenylephrine inhibits myometrium contraction in mice, with an IC 50 of approximately 10 − 6 M through activation of the β 2 -receptor in a concentration-dependent manner [ 8 ]. Our experimental findings were similar to this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study have confirmed that phenylephrine can inhibit isolated myometrium contraction in mice by activating the β 2 receptor [ 8 ]. In in vivo experiments, it has also been reported that endogenously released epinephrine attenuates pulmonary vasoconstriction and bronchoconstriction in systemic allergic reactions in Sprague-Dawley rats by activating β 2 -adrenergic receptors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%